2008
DOI: 10.1016/j.bcp.2008.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of changes in the proteome of HL-60 promyeloid leukemia cells induced by the proteasome inhibitor PSI

Abstract: Proteasome inhibitors display potent anti-neoplastic and anti-angiogenic properties both in vitro and in vivo. The mechanisms, however, by which proteasome inhibitors kill tumor cells are still fairly elusive as is the molecular basis of resistance to treatment. To address these questions, we employed a high-throughput Western blotting procedure to analyze changes in a subproteome of ~800 proteins in the promyelocytic leukemia cell line HL-60 upon treatment with the proteasome inhibitor PSI (ZIle-Glu(OtBu)-Ala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
2
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 61 publications
(62 reference statements)
3
2
0
Order By: Relevance
“…These findings together with our previously results for anthraquinone antitumour agents (DOX, pirarubicin and benzoperimidine BP1) and data published by other groups (e.g. for curcumin, UVC irradiation and proteasome inhibitor Z‐Ile‐Glu(OtBu)‐Ala‐Leu‐aldehyde (PSI)) strongly suggest that even though the studied sensitive HL60 cells and MDR cells (HL60/VINC and HL60/DOX) undergo apoptosis in response to anthraquinone antitumour agents and other cellular stress stimuli, they are also able to activate non‐apoptotic cell death pathways in response to some anticancer compounds (e.g. CO1).…”
Section: Discussionsupporting
confidence: 85%
“…These findings together with our previously results for anthraquinone antitumour agents (DOX, pirarubicin and benzoperimidine BP1) and data published by other groups (e.g. for curcumin, UVC irradiation and proteasome inhibitor Z‐Ile‐Glu(OtBu)‐Ala‐Leu‐aldehyde (PSI)) strongly suggest that even though the studied sensitive HL60 cells and MDR cells (HL60/VINC and HL60/DOX) undergo apoptosis in response to anthraquinone antitumour agents and other cellular stress stimuli, they are also able to activate non‐apoptotic cell death pathways in response to some anticancer compounds (e.g. CO1).…”
Section: Discussionsupporting
confidence: 85%
“…In agreement with previously published results (Choi et al 2008), we have also shown that the bortezomib induced proteolytic activation of procaspase 3 in HL-60 cells manifested by the increase of p17 fragment of active caspase 3. In K562 cells, the bortezomib-induced decrease of procaspase 3 was not associated with the production of p17 fragment of caspase 3.…”
Section: Discussionsupporting
confidence: 93%
“…Instead of this, we have shown that the bortezomib induced cleavage of HSP90β through the action of caspase 8. This is in agreement with previous studies that have documented activation of caspase 8 after the incubation of different cancer cells with proteasome inhibitors (Colado et al 2008;Laussmann et al 2011;Fiandalo et al 2013) including HL-60 cells (Choi et al 2008). Since it has been documented that HSP90β is a substrate of caspase 10 but not caspase 8 (Chen et al 2009), we assume that caspase 8 is the initiator of this process while caspase 10 is responsible for direct cleavage of HSP90β.…”
Section: Discussionsupporting
confidence: 93%
“…So far, very few proteomic studies have attempted to investigate the global cellular response to proteasome inhibition . Immunoblotting techniques have been widely used to measure protein abundance upon proteasome inhibition, but this strategy is restricted to well‐known pathway due to the availability of specific antibodies . One of the first large‐scale mass spectrometry (MS)‐based proteomic studies to decipher mechanism of proteasome inhibitors was performed in our lab by Uttenweiller and colleagues, and reported the effect of bortezomib on both differentiated and undifferentiated Acute Promyelocytic Leukemia (APL) cells and revealed that the differential apoptotic effects of bortezomib on these particular cells are mainly due to distinct protein toxicity levels .…”
Section: Introductionmentioning
confidence: 99%